PTTG1-DLX2 axis drives malignant progression of lung adenocarcinoma by activating the WNT/β-catenin signaling pathway - Chen, Huili; Zhang, Xinyu; Lian, Xiaofu; Wang, Ziqiang; Zhang, Feiyue; Zhang, Jing; Min, Shengping; Yang, Shasha; Wang, Xiaojing; Lian, Chaoqun (Translational Cancer Research, 2026)
Lung adenocarcinoma (LUAD) remains a leading cause of cancer mortality, and the molecular drivers that promote its malignant progression are not fully characterized. This study aimed to define the oncogenic function of pituitary tumor transforming gene 1 (PTTG1) in LUAD and to elucidate its mechanistic relationship with distal-less homeobox 2 (DLX2) and the WNT/β-catenin signaling pathway.